(3TQM eTcdGJ OjhGf CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3eMeO UGdM GdTQja s)
(3ChdgG (B:s
(3LGRjJfi CjOc Gddg CeQ TYQ CHj JeGe MHjH Hf ChS GdWGFi heG ajg ef JYhjV GdCHjGJ hHOjY GdeYGfi hGdCdaGX s
(3BNQgG (B:s
(3abO MQaJ ODhHi ai JMUjdg hYfGfi ai LeYg hJCdja , hYjQgG GdLfS ai ReGffG gPG s
(3CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFi GdeJhai (B231(3g`s
(3HBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs